Lord of misrule [videorecording (DVD)] - De Ville, Tom; Ineson, Ralph, 1969-; Middleton, Tuppence, 1987-; Stokoe, Matt, 1989-; Goodall, Alexa; Detar, Brett, 1978- (Magnolia Home Entertainment, 2024)
A desperate search ensues when the young daughter of a rural village's vicar goes missing. Discovered in the grip of evil, the vicar must decide how much she is willing to risk in order to save her daughter.